(untitled) (Ingenieria y Universidad, 2002)
This paper presenis the process of image analusis deoeiopeci to study the behavior 01myocardium cells in experiments, where a substance is added to induce changes on observed ceils; the idea is to observe and measure these changes. To achieve this objective, an ordered collection of images must be acquired and onaujzed as a ushoie. This work aims to automate the research work in the CeH Physiology Laboratory of the Colombiari Naiionai Healin. Institute. The main characteristics to observe are the ceü morpholoqicai and chromatic changes over time. The image processing petfottns the segmentation and characterization of each cell to build a cell history at different poinis during the process. For an individual imaqe, this process includes background segmentation, cell segmentation, feature extraction and cell filtering. For the set of images the process includes cell matching, cell history construction and global analysis. This paper explains briejly the whole process; we jocus the discussion in the presentation and analysis of the experimental results.